An Extensive Photometric Investigation of the W UMa System DK Cyg. (15th January 2015) - Elkhateeb, M. M.; Nouh, M. I.; Elkholy, E.; Korany, B.
Abstract : DK Cyg( P = 0.4707 ) is a contact binary system that undergoes complete eclipses. All the published photoelectric data have been collected and utilized to reexamine and update the period behavior of the system. A significant period increase with rate of 12.590 × 10 −11 days/cycle was calculated. New period and ephemeris have been calculated for the system. A long term photometric solution study was performed and a light curve elements were calculated. We investigated the evolutionary status of the system using theoretical evolutionary models.